Effect of Deep Brain Stimulation on Swallowing Function: A Systematic Review - Yu, Huiyan; Takahashi, Kazutaka; Bloom, Lisa; Quaynor, Samuel D.; Xie, Tao (Frontiers in Neurology, 2020)
The effect of deep brain stimulation (DBS) on swallowing function in movement disorders is unclear. Here, we systematically reviewed this topic by searching keywords following PICOS strategy of problem (swallowing or swallow or dysphagia or aspiration) and intervention (deep brain stimulation, or DBS) in the PubMed and Web of Science in English in April 2020, with comparators (subthalamic nucleus, STN; globus pallidus interna, GPi; ventralis intermedius, ViM; post-subthalamic area or caudal zona incerta, PSA/cZi; ON/OFF DBS state/settings; ON/OFF medication state; Parkinson’s disease or PD; dystonia; tremor), outcomes (swallowing function measures, subjective/objective) and study types (good quality original studies) in mind. We found that STN DBS at usual high frequency stimulation could have beneficial effect (more so on subjective measures and/or OFF medication), no effect, or detrimental effect (more so on objective measures and/or ON medication) on swallowing function in patients with PD, while low frequency stimulation could have beneficial effect on swallowing function in patients with freezing of gait. GPi DBS could have a beneficial effect (regardless of medication state and outcome measures) or no effect, but no detrimental effect, on swallowing function in PD. GPi DBS also has beneficial effects on swallowing function in majority of the studies on Meige syndrome but not in other diseases with dystonia. PSA/cZi DBS rarely has detrimental effect on swallowing functions in patients with PD or tremor. There is limited information on ViM to assess. Information on swallowing function by DBS remains limited. Well-designed studies and direct comparison of targets are further needed.